MANAJEMEN EKSTRAKURIKULER PRAMUKA DALAM MENINGKATKAN MINAT DAN BAKAT PESERTA DIDIK DI MTS AT-TAQWA SAMARINDA - Badrut Tamam; Muhammad Taufiqurrahman; Bahrani; Sudadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education in Indonesia currently has not fully met the expectations of the community, marked by the low quality of graduates and the resolution of educational problems that have not been fully resolved. Various efforts continue to be made, by making improvements through extracurricular activities, one of which is Scouting. The study aims to determine the management of Scouting Extracurricular in increasing the interests and talents of students at MTs At-Taqwa Samarinda, and to identify supporting and inhibiting factors. This study uses a descriptive qualitative method and George R. Terry's management theory which includes the functions: planning, organizing, actuating, and controlling. The results of the study indicate that the management of Scouting Extracurricular is carried out well, starting from planning through the syllabus and policies in Document 1 of the madrasah, organizing with a formal structure, implementing activities according to the syllabus by focusing on developing student abilities both in the field of scouting and in other fields, to monthly evaluations carried out in the last week of each month and annual evaluations in the form of camps and competitions and exams at the end of each semester. Supporting factors: support from the head of the madrasah, written policies, and annual activities. Inhibiting factors: fluctuating student interest, parental permission, minimal budget, and inadequate facilities and infrastructure.